Dampak proses evaluasi strategi terhadap keunggulan kompetitif diindustri bri syariah - nisa, fitria izzatun (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the impact of the strategy evaluation process on the competitive advantage of BRI Syariah, one of the leading Islamic banks in Indonesia. In the competitive Islamic banking industry, it is important for BRI Syariah to be able to adjust the strategies implemented to remain relevant and superior in the market. Strategy evaluation plays a key role in identifying internal strengths and weaknesses, as well as external opportunities and threats, allowing for more adaptive and responsive strategy adjustments to market changes. The results of the study show that the strategy evaluation process contributes significantly to improving the quality of products and services offered by BRI Syariah. By understanding customer needs and market trends through in-depth analysis, banks can develop innovative products that are in line with sharia principles, such as microfinance for small and medium-sized enterprises. In addition, the periodic evaluation of strategies allows BRI Syariah to be more responsive to market and regulatory changes and strengthens its position in the Islamic banking industry. Overall, this study confirms that systematic and sustainable strategy evaluation is the key for BRI Syariah to maintain and improve its competitive advantage in the midst of increasingly fierce industry competition. Thus, BRI Syariah can continue to provide more value to customers and maintain its existing market share, as well as expand its reach in the Indonesian Islamic banking market.